In vitro and in silico pharmaco-nutritional assessments of some lesser-known Nigerian nuts: Persea americana, Tetracarpidium conophorum, and Terminalia catappa - Efah Denis Eyong; Iwara Aripko Iwara; Eyuwa Ignatius Agwupuye; Abdulhakeem Rotimi Agboola; Daniel Ejim Uti; Wilson Arong Obio; Esther Ugo Alum; Item Justin Atangwho (PLoS ONE, 2025)
Together with their nutritional qualities, the biosafety, antidiabetic, antioxidant, and anti-inflammatory effects of Tetracarpidium conophorum nuts, Persea americana seeds, and Terminalia cattapa kernels were evaluated in vitro and in silico. RBC membrane stabilisation for anti-inflammatory characteristics, antioxidant activities by ABTS, DPPH, H2O2, and nitric oxide scavenging assays, and α-glucosidase and α-amylase inhibitory assays conducted in vitro were used to evaluate the anti-diabetic activity. With an IC50 value of 208 μg/mL, P. americana showed the maximum amount of inhibition, according to the results, while T. catappa showed a somewhat lower degree of inhibition at 236 μg/mL. P. americana exhibited the highest degree of α-amylase inhibition, with an IC50 value of 312 µg/mL. T. catappa showed the strongest DPPH radical scavenging activity, while T. conophorum showed the highest ABTS radical scavenging activity. T. catappa showed the strongest effectiveness in neutralising hydrogen peroxide. In tests using human red blood cells, T. catappa showed the strongest inhibition of RBC hemolysis. While P. americana showed higher concentrations of copper, manganese, potassium, and calcium, T. catappa showed higher magnesium concentrations. T. catappa had considerably higher levels of ash, proteins, lipids, and carbohydrates than T. conophorum, which had the highest quantity of crude fibre, according to proximate analysis. Molecular docking experiments have revealed that plant extracts from P. americana, T. conophorum, and T. catappa have substantial binding affinities towards α-glucosidase and amylase. Pseudococaine, M-(1-methylbutyl) phenylmethylcarbamate, o-xylene, and 1-deoxynojirimycin were the four compounds that showed binding affinities that were higher than those of acarbose. Acarbose and nitrate were not as compatible with docking scores as compared to the compounds dimethyl phthalate, pseudococaine, M-(1-Methylbutyl)phenyl methylcarbamate, 2-chloro-3-oxohexanedioic acid, and methyl 2-chloro-5-nitrobenzoate. These results suggest that these plant extracts hold great potential for the creation of therapeutic medications that specifically target oxidative stress-related diseases like diabetes.